‘SOFT’ SUPPORT INFRASTRUCTURE AND THE PERFORMANCE OF SMALL AND MEDIUM-SIZED ENTERPRISES IN EUROPEAN COUNTRIES - Ćudić, Bojan; Skrodzka, Iwona (Economic Annals, 2021)
The purpose of this paper is to examine the relationship between ‘soft’ support infrastructure (SSI) and the performance of small and medium enterprises (SMEs). The study encompasses European countries’ economic activity and SMEs’ output in 2015 and 2018. The focus of the research is SMEs in the European Union member states and the Western Balkan countries. The analysis was conducted using partial least squares structural equation modelling (PLS-SEM). This method enabled the examination of links between variables that are not directly observable. The results show that countries investing in SSI have better SME performance. Based on the statistical analysis, among other things, the authors identify the Human Development Index and the use of information and communication technology at the company level as the two most significant factors that impact on SMEs’ performance.